Hollow microcapsule with pH-sensitive chitosan/polymer shell for in vitro delivery of curcumin and gemcitabine. (5th January 2022) - Kazemi-Andalib, Faeze; Mohammadikish, Maryam; Divsalar, Adeleh; Sahebi, Unes
Graphical abstract: Highlights: Preparation of the hollow capsule via the LbL method and subsequent core removal. Higher release of the trapped drug at acidic pH. Potential cytotoxicity effect of the prepared drug carrier on the HCT-116 cells. Abstract: The utilization of hollow structures for encapsulation and controlled release of drugs has attracted considerable attention in recent years. Among the different methods reported for fabrication of hollow polymer microcapsules, the layer-by-layer (LbL) assembly of oppositely charged polymers is of special importance. The pH-responsive capsules have attracted special interest as anti-cancer drug delivery systems due to the difference between normal and cancerous tissue. In this work, new pH-sensitive and biodegradable capsules were prepared based on the layer-by-layer (LbL) assembly of oppositely charged polyelectrolytes, chitosan (CS), and poly(ethylene glycol dimethacrylate-co-methacrylic acid) (EM). The obtained microcapsules were used for the delivery of two types of anticancer drugs including gemcitabine (Gem) and curcumin (Cur). The removal of the core was proved with transmission electron microscopy (TEM) confirming the spherical shape of the prepared hollow structure. The high performance of microcapsules was proven by encapsulation efficiency (EE%) and releasing efficiency (RE%) of above 84% and 82%, respectively. The high pH sensitivity of prepared microcapsules is due to the solubility of chitosan in acidic media. These microcapsules exhibit high cytotoxicity in a dose-dependent manner on the HCT-116 colorectal carcinoma cells. On the other hand, the desired results for the drug delivery of Gem and Cur demonstrate the applicability of prepared microcapsules for different drugs.